2020
DOI: 10.1039/c9cs00285e
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-functionalized hydrogels: biomimetic design, adhesion mechanism, and biomedical applications

Abstract: This review presents insights into the fundamental challenges of wet adhesion, and the applications of catechol-functionalized hydrogels in diverse areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
529
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 642 publications
(532 citation statements)
references
References 249 publications
(334 reference statements)
3
529
0
Order By: Relevance
“…At the same time, the hydrogel preparation method is simple and easy to operate during the preparation process, and has long-term stability, which greatly expands the application of hydrogels in underwater or humid environments, especially in the potential of body fluids or blood environments [ 95 ]. Zhang et al [ 96 ] summarized the technical difficulties in the underwater adhesion of hydrogel materials, focused on the relevant parameters that characterize the underwater mechanical properties of hydrogels, and established the experimental design and evaluation methods for hydrogel materials based on this, and summarized the unique properties, synthesis method, and preparation process of the biomimetic viscous hydrogel, and proposed new insights into the underwater adhesion mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the hydrogel preparation method is simple and easy to operate during the preparation process, and has long-term stability, which greatly expands the application of hydrogels in underwater or humid environments, especially in the potential of body fluids or blood environments [ 95 ]. Zhang et al [ 96 ] summarized the technical difficulties in the underwater adhesion of hydrogel materials, focused on the relevant parameters that characterize the underwater mechanical properties of hydrogels, and established the experimental design and evaluation methods for hydrogel materials based on this, and summarized the unique properties, synthesis method, and preparation process of the biomimetic viscous hydrogel, and proposed new insights into the underwater adhesion mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…As the promising drug carriers, hydrogels have been experiencing fast development in recent years (Lai and He, 2016 ; Oliva et al, 2017 ). With the retained large amounts of water and excellent biocompatibility, hydrogels demonstrated useful tool for targeted drug delivery and controlled drug release (Li and Mooney, 2016 ; Lei et al, 2018 ; Huang et al, 2020 ; Zhang et al, 2020a ). According to the cross-linking methods, hydrogels can be formed through non-covalent physical interactions or covalent chemical bonds (Goujon et al, 2017 ; Gu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This initiates a polymerization reaction, which makes catecholfunctionalized polymers suitable for oxidation-mediated hydrogel crosslinking. [94] Seminal work from Lee et al showed the gelation of dopamine-functionalized, multiarm PEG upon the addition of an oxidizing agent, sodium periodate. [95] Similarly, the addition of sodium periodate was able to induce the gelation of catechol-terminated poly(p-phenylene oxide)/ PEG, [96] gelatin, [97] recombinant fp-1 mussel adhesive protein, [98] and HA.…”
Section: Change In Oxidation Statementioning
confidence: 99%